Moessbauer study of the behaviour of sinthetic corrosion products of nuclear power plants - Blesa, Miguel A.; Maroto, Alberto; Passaggio, Susana Irene; Labenski, Felisa; Saragovi de Badler, Celia (Pergamon Press, 1978)
Fil: Blesa, Miguel A. Comisión Nacional de Energía Atómica; Argentina